EKSPLORASI KONSEP MATEMATIKA NON-GEOMETRIS DALAM KEGIATAN PRAMUKA MELALUI PENDEKATAN ETNOMATEMATIKA - Samsia Laitupa; Djaffar Lessy; Patma Sopamena (PHI: Jurnal Pendidikan Matematika, 2026)
Mathematics learning should not only transfer knowledge but also facilitate students in building new concepts relevant to culture and everyday experiences. Ethnomathematics as a learning approach links mathematics with cultural elements, thus facilitating contextual and meaningful conceptual understanding. This research aims to investigate non-geometric mathematical practices embedded within Scout pioneering activities at Madrasah Aliyah Nurul Ikhlas Ambon, employing a qualitative ethnographic methodology. Data were gathered through participatory observation and in-depth interviews with mentors, trainers, and students. The study found that pioneering practices incorporate mathematical elements such as measurement, estimation, knotting algorithms, and structural proportions, all of which are enriched with cultural significance. These activities contribute not only to the development of mathematical understanding but also foster essential character values, including collaboration, accountability, and creativity. The findings support the use of pioneering ethnomathematics as supporting material for contextual mathematics learning in accordance with the direction of the Independent Curriculum policy. It is recommended to develop learning tools based on Scout ethnomathematics to increase students' interest and conceptual understanding.